Diary of a wimpy kid : the third wheel - Kinney, Jeff. (New York : Amulet Books, 2012)
As the day of the Valentine's Day dance approaches, Greg Heffley worries he will be left out until a twist of fate lands Greg with a date, but leaves his best friend, Rowley, on his own.
5.0
5-8.
5-8
Keywords: Best friends -- Juvenile fiction; Dance -- Juvenile fiction; Diaries -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Valentine's Day -- Juvenile fiction; Best friends -- Fiction; Dance -- Fiction; Diaries -- Fiction; Humorous stories; Middle schools -- Fiction; Schools -- Fiction; Valentine's Day -- Fiction; Dance -- Fiction; Diaries -- Fiction; Friendship -- Fiction; Humorous fiction; Middle schools -- Fiction; School stories; Valentine's Day -- Fiction; Humorous fiction